Portrayal of Professional Digital Competence (PDC) of English Teacher: Digital Immigrant vs. Native - Imam Santosa; Ifan Iskandar (UNIB Press, 2023)
This study aimed to investigate the differences in professional development for digital competence (PDC) levels between digital immigrant and digital native teachers. A total of 49 teachers participated in the study. Data was collected through an online survey that measured their PDC levels in seven domains: Subject and Basic Skills, School in Society, Ethics, Pedagogy and Subject Didactics, Leadership of Learning Processes, Interaction and Communication, and Change and Development. The results indicated that there were slight differences between the PDC levels of digital immigrant and digital native teachers. Digital immigrant teachers had higher percentages at the none level and the skills level, while digital native teachers had higher percentages at the knowledge level and the competence level. The findings suggest that both groups of teachers have relatively high levels of PDC, indicating that they are capable of using technology effectively in their teaching practices. The study highlights the importance of ongoing professional development for both groups to ensure they are equipped with the necessary digital competencies to effectively support their students in the digital age. The PDC framework can be a useful tool for identifying areas of strength and weakness for both digital learner groups, and can guide the development of targeted professional development programs.